Measurement and evaluation in human performance - Morrow, James R. 1947- (Human Kinetics, 2005)
Measurement and Evaluation in Human Performance, Third Edition, offers unmatched, in-depth instruction in measurement and evaluation techniques. Thoroughly revised and updated, the third edition features a new section on epidemiology and further develops international perspectives. This edition features improved readability in measurement statistics and enhanced efficiency in solving measurement and evaluation problems when using the Statistical Package for the Social Sciences (SPSS).